Penerapan Model Problem Based Learning Untuk Meningkatkan Hasil Belajar Siswa Kelas X SMA Negeri 3 Kota Kupang Pada Materi Trigonometri Dengan Berbantuan Power Point Interaktif - Mendes, Ivona Lydia; Samo, Damianus D.; Madu, Aleksius (Fraktal : Jurnal Matematika dan Pendidikan Matematika, 2025)
This study is based on the low student learning outcomes in trigonometry material. This study aims to describe the improvement of learning outcomes of class X students of SMA Negeri 3 Kota Kupang by applying the Problem Based Learning model on trigonometry material with the help of interactive power point. This research was conducted with research procedures based on the Kemmis and Mc. Taggart model which consists of four research components, namely plan, act, observe, and reflect. The data collection techniques were observation and tests. The instruments used were teacher and student observation sheets and learning outcome test sheets. The results of this study showed that the classical student learning outcomes in cycle I were 63.33% which increased to 83.33% in cycle II. Meanwhile, the observation result of teacher activity while teaching in cycle I obtained a percentage of 93.1% seen to increase to 97,9% in cycle II and the observation result of student activity during the learning process in cycle I obtained a percentage of 86.8% increased to 95,8% in cycle II. Therefore, the application of problem-based learning model on trigonometry material with the help of interactive power point can improve the learning outcomes of students of class X SMA Negeri 3 kupang city.